Watershed infarcts in a patient after carotid endarterectomy. (8th October 2012) - Hashmi, Imranullah; Shahzadi, Fatima
Abstract : We report a case that developed watershed infarcts after undergoing carotid endarterectomy. Our patient had been having episodes of transient ischaemic attacks before admission. Carotid Doppler scan before admission showed severe unilateral carotid stenosis on left side. She underwent a carotid endarterectomy procedure. Her continuous blood pressure monitoring stayed normal during and after the procedure. One and half hour after the procedure, she developed right arm weakness. CT scan later revealed watershed infarcts in left cerebral hemisphere. The pathogenesis of watershed infarcts remain debated despite haemodynamic and embolic mechanisms being postulated.